Vestibular assessment in children with sensorineural hearing loss: diagnostic accuracy and proposal for a diagnostic algorithm - Gerdsen, Max; Hundscheid, Tamara Maria; Boudewyns, An; Van Rompaey, Vincent; Van De Berg, Raymond; Widdershoven, Josine Christine Colette (Frontiers in Neurology, 2024)
Introduction: Vestibular assessment in children with sensorineural hearing loss (SNHL) is critical for early vestibular rehabilitation therapy to promote (motor) development or guide decision making towards cochlear implantation (timing of surgery and laterality). It can be challenging from a clinical viewpoint to decide which vestibular tests should be performed for a pediatric patient. The aim of this study was to evaluate the diagnostic accuracy of several clinically available vestibular tests in children with SNHL, and to provide recommendations for the implementation of vestibular testing of children in clinical practice, to screen for vestibular hypofunction (VH).Methods: A two-center retrospective chart review was conducted. Eighty-six patients between the age of 0 and 18 years were included in this study with SNHL. Vestibular tests included video headimpulse test (VHIT), caloric test (performed at the age of four or higher), rotatory chair and cervical vestibular evoked myogenic potential (cVEMP). A combination of the clinical assessment and (combinations of) vestibular test outcomes determined the diagnosis. The diagnostic quality of tests and combination of tests was assessed by diagnostic accuracy, sensitivity and specificity.Results: VH was diagnosed in 44% of the patients. The VHIT and caloric test showed the highest diagnostic accuracy compared to the rotatory chair and cVEMP. All combinations of VHIT, caloric test and cVEMP showed improvement of the diagnostic accuracy compared to the respective tests when performed singularly. All combinations of tests showed a relatively similar diagnostic accuracy, with the VHIT combined with the caloric test scoring the highest. Adding a third test did not substantially improve the diagnostic accuracy. Discussion: Vestibular testing is feasible and VH is highly prevalent in children with SNHL. A proposed diagnostic algorithm recommends starting with VHIT, followed by cVEMP for children under the age of four, and caloric testing for older children if VH is not confirmed with the first test. Performing a third test is redundant as the diagnostic accuracy does not improve substantially. However, challenges remain, including the lack of a gold standard and the subjective nature of the diagnosis, highlighting the need for standardized testing and increased understanding of VH in this population.